Evidence for efficient regenerated production and dinitrogen fixation in nitrogen-deficient waters of the South Pacific Ocean: impact on new and export production estimates - P. Raimbault; N. Garcia (Biogeosciences, 2008)
One of the major objectives of the BIOSOPE cruise, carried out on the R/V Atalante from October-November 2004 in the South Pacific Ocean, was to establish productivity rates along a zonal section traversing the oligotrophic South Pacific Gyre (SPG). These results were then compared to measurements obtained from the nutrient – replete waters in the Chilean upwelling and around the Marquesas Islands. A dual 13C/15N isotope technique was used to estimate the carbon fixation rates, inorganic nitrogen uptake (including dinitrogen fixation), ammonium (NH4) and nitrate (NO3) regeneration and release of dissolved organic nitrogen (DON). The SPG exhibited the lowest primary production rates (0.15 g C m−2 d−1), while rates were 7 to 20 times higher around the Marquesas Islands and in the Chilean upwelling, respectively. In the very low productive area of the SPG, most of the primary production was sustained by active regeneration processes that fuelled up to 95% of the biological nitrogen demand. Nitrification was active in the surface layer and often balanced the biological demand for nitrate, especially in the SPG. The percentage of nitrogen released as DON represented a large proportion of the inorganic nitrogen uptake (13–15% in average), reaching 26–41% in the SPG, where DON production played a major role in nitrogen cycling. Dinitrogen fixation was detectable over the whole study area; even in the Chilean upwelling, where rates as high as 3 nmoles l−1 d−1 were measured. In these nutrient-replete waters new production was very high (0.69±0.49 g C m−2 d−1) and essentially sustained by nitrate levels. In the SPG, dinitrogen fixation, although occurring at much lower daily rates (≈1–2 nmoles l−1 d−1), sustained up to 100% of the new production (0.008±0.007 g C m−2 d−1) which was two orders of magnitude lower than that measured in the upwelling. The annual N2-fixation of the South Pacific is estimated to 21×1012g, of which 1.34×1012g is for the SPG only. Even if our "snapshot" estimates of N2-fixation rates were lower than that expected from a recent ocean circulation model, these data confirm that the N-deficiency South Pacific Ocean would provide an ideal ecological niche for the proliferation of N2-fixers which are not yet identified.